Analogical Reasoning in Ethics - Spielthenner, Georg (Ethical theory and moral practice, 2014)
In this article I am concerned with analogical reasoning in ethics. There is no doubt that the use of analogy can be a powerful tool in our ethical reasoning. The importance of this mode of reasoning is therefore commonly accepted, but there is considerable debate concerning how its structure should be understood and how it should be assessed, both logically and epistemically. In this paper, I first explain the basic structure of arguments from analogy in ethics. I then discuss the diversity of analogical arguments that can be found in ethics. I analyse their structure, assess them from a logical viewpoint, and show how they can be epistemically challenged and defended. The result of this investigation is that, contrary to a commonly held view, analogical reasoning can be a logically valid type of ethical reasoning that can provide reasons for action that are not worse than the reasons provided by any other kind of practical reasoning.